Whole Blood Transfusion for Severe Malarial Anemia in a High Plasmodium falciparum Transmission Setting. (19th April 2022) - Ippolito, Matthew M; Kabuya, Jean-Bertin B; Hauser, Manuela; Kamavu, Luc K; Banda, Proscovia Miiye; Yanek, Lisa R; Malik, Rubab; Mulenga, Modest; Bailey, Jeffrey A; Chongwe, Gershom; Louis, Thomas A; Shapiro, Theresa A; et al.
Abstract: Background: Severe malaria resulting from Plasmodium falciparum infection is the leading parasitic cause of death in children worldwide, and severe malarial anemia (SMA) is the most common clinical presentation. The evidence in support of current blood transfusion guidelines for patients with SMA is limited. Methods: We conducted a retrospective cohort study of 911 hospitalized children with SMA in a holoendemic region of Zambia to examine the association of whole blood transfusion with in-hospital survival. Data were analyzed in adjusted logistic regression models using multiple imputation for missing data. Results: The median age of patients was 24 months (interquartile range, 16–30) and overall case fatality was 16%. Blood transfusion was associated with 35% reduced odds of death in children with SMA (odds ratio, 0.65; 95% confidence interval, .52–.81; P = .0002) corresponding to a number-needed-to-treat (NNT) of 14 patients. Children with SMA complicated by thrombocytopenia were more likely to benefit from transfusion than those without thrombocytopenia (NNT = 5). Longer storage time of whole blood was negatively associated with survival and with the posttransfusion rise in the platelet count but was not associated with the posttransfusion change in hemoglobin concentration. Conclusions: Whole blood given to pediatric patients with SMA was associated with improved survival, mainly among those with thrombocytopenia who received whole blood stored for <4 weeks. These findings point to a potential use for incorporating thrombocytopenia into clinical decision making and management of severe malaria, which can be further assessed in prospective studies, and underline the importance of maintaining reliable blood donation networks in areas of high malaria transmission. Abstract : A retrospective observational study in northern Zambia of pediatric patients with severe malarial anemia examined the impact of whole blood transfusion on survival. Transfusion was associated with greater survival, and thrombocytopenia was significantly associated with mortality and transfusion response.